AN ANALYSIS TYPES OF SLANG AND PROCESS WORD FORMATION IN SONG LYRIC BY BRUNO MARS IN THE “DOO-WOPS & HOOLIGANS” ALBUMS - I Kadek Iwan Gunadi; Ni Wayan Suastini (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The entitled this study is “Analysis Types of Slang and Process Word Formation in Song Lyric by Bruno Mars of the Doo-Wops & Hooligans Album”. The purpose of this study was to identify the types of slang and the word formation process found on Doo-Wops & Hooligans albums, including Somewhere in Brooklyn, Count on Me, The Other Side, The Lazy Song, Talking to the Moon, Our First Time, Just the Way You Are (Remix), Runaway Baby, Just the Way You Are, Grenade, Liquor Store Blues, and Marry You. In this study, the method used is descriptive qualitative and uses observation techniques. This analysis uses the theory from Kipfer and Chapman (2007: 8) to identify types of slang and Mattiello theory (2008: 72-154) to analyze the process of word formation in 12 song in the album there are many slang words in the lyrics of this song, so this research uses the song by Bruno Mars as its research.